2007
DOI: 10.3928/02793695-20070101-09
|View full text |Cite
|
Sign up to set email alerts
|

Relocation Stress Syndrome in Older Adults Transitioning from Home to a Long-Term Care Facility: Myth or Reality?

Abstract: <p>Relocation stress syndrome is a nursing diagnosis characterized by symptoms such as anxiety, confusion, hopelessness, and loneliness. It usually occurs in older adults shortly after moving from a private residence to a nursing home or assisted-living facility. The primary purpose of this study was to validate the symptoms of relocation stress syndrome. Eight nursing home residents and 8 assisted-living facility residents were interviewed 2 to 10 weeks after admission, when symptoms of relocation stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 11 publications
5
38
0
Order By: Relevance
“…The wish for their partner or spouse to come live in the facility and their efforts to communicate and interact with other residents in the LTC facility with the view of making friendships also strongly indicate the wish to avoid alienation. Consistent with findings from other studies, we found that the stress experienced by the elderly when they relocated to LTC facilities could originate from different factors [37][38][39]. The elderly in our study felt threatened by their loss of autonomy and their ability to perform self-care; feeling of dislike and distrust of the care provider and facility; fear of neglect and concerns about overall safety from injuries and accidents; feelings of missing their home and families; unfamiliar or uncomfortable environment.…”
Section: Discussionsupporting
confidence: 89%
“…The wish for their partner or spouse to come live in the facility and their efforts to communicate and interact with other residents in the LTC facility with the view of making friendships also strongly indicate the wish to avoid alienation. Consistent with findings from other studies, we found that the stress experienced by the elderly when they relocated to LTC facilities could originate from different factors [37][38][39]. The elderly in our study felt threatened by their loss of autonomy and their ability to perform self-care; feeling of dislike and distrust of the care provider and facility; fear of neglect and concerns about overall safety from injuries and accidents; feelings of missing their home and families; unfamiliar or uncomfortable environment.…”
Section: Discussionsupporting
confidence: 89%
“…The wish for their partner or spouse to come live in the facility and their efforts to communicate and interact with other residents in the LTC facility with the view of making friendships also strongly indicate the wish to avoid alienation. Consistent with ndings from other studies, we found that the barriers experienced by the elderly when they relocated to LTC facilities could originate from different factors [46][47][48]. The elderly in our study felt threatened by their loss of autonomy and their ability to perform self-care; feeling of dislike and distrust of the care provider and facility; fear of neglect and concerns about overall safety from injuries and accidents; feelings of missing their home and families; unfamiliar or uncomfortable environment.…”
Section: Discussionsupporting
confidence: 89%
“…A fourth possible limitation is that cognitive status of residents was not assessed prior to admission, but shortly after. However, numerous studies indicate that cognitive status is not significantly influenced by transition to a nursing home facility (Engle, 1985;Walker et al, 2007). Therefore, we considered the MMSE score at the first measurement to be indicative of cognitive status shortly before admission.…”
Section: Discussionmentioning
confidence: 99%